La potencia en el salto vertical en adolescentes - Aviles Lopez, Charlye Leo (2025)
In the present research work, it was proposed to determine the effect that a specific potency program of the lower body has on the vertical jump in adolescents of 15 and 16 years old about the cantonal league of Chambo, taking into account that this type of training programs have as an objective the integral physical development of the adolescents to provide them with long-term benefits, as well as to improve at a sporting level to meet the current physical demands that sports require. The techniques and instruments used for data collection were the Sargent Test of vertical jump and a data collection form. After analyzing the data in the statistical program IBM SPSS Statistics 26, the student’s t-test applied to the data gave us a bilateral significance of 0.00; thanks to this result, we could conclude that the potency program developed had positive effects concerning the vertical jump of the adolescents.